Pengembangan Media Pembelajaran SD - Zahzia Kurnia Putri; Irene Diaz Maura; Muhammad Hafizt Ajjruraffi Sauqi; Humaysah Humaysah; Wismanto Wismanto (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Learning media is a vehicle for transmitting learning messages and information. Learning media is designed as best as possible to improve student learning outcomes. In this era of globalization, learning media is increasingly advanced. The use of Information Technology as a learning medium has become a demand. In order to increase the effectiveness and efficiency of learning, various creative and innovative learning models need to be developed. This research aims to meet school needs, increase interest in learning and improve student learning outcomes. Limitations of learning media are known to be one of the obstacles that exist in learning at the elementary school level, especially for students. The impact of limited media is the low interest and activity of students when participating in elementary school learning. The existence of these obstacles aims to develop Monokebu media as an alternative solution to learning problems for students as well as finding out whether the media is suitable for use in learning and presenting the results of limited trials of the media. The method used in this research is a qualitative method with a library research approach. The results of this research indicate that it is very necessary to develop teaching material media to improve student learning outcomes. In this progressive era, learning media can be created using technology-based learning media models. Among the technology-based media are PPT, Google Classroom, Google Meet. Including Monokebu media.